Influência do tempo de inundação, multiplas tides e intensificação da nitrificação em um sistema de wetlands construido tidal flow tratando água de corrego urbano na remoçao do etinilestradiol e triclosan - Svenar, Silvana (2023)
Emerging contaminants have been a constant concern, as they are increasingly present in the environment, including 17α-ethinyl estradiol (EE2) and triclosan (TCS), which, even at low concentrations, can potentially cause severe risks to living organisms. Faced with the lack of coverage of sanitation infrastructure or even the current system’s inefficiency, investing in alternative treatment processes such as constructed wetlands can be an economically and environmentally viable alternative. In this study, the behavior of a constructed tidal flow wetland system (WCTF) was evaluated in the removal of emerging contaminants 17α-ethinyl estradiol and triclosan, carbonaceous, nitrogenous and phosphorous organic matter, as well as their influence on the structure of the microbial community. The system operated for 223 days under variation of flooding time, amount of tides and intensification of the nitrification process. As support material, the residue of civil construction material (red ceramic block fragments) was used and planted with the macrophyte Althernanthera philoxeroides. The results were raised through the analysis of 4 operational stages: the first two stages with only one tide, varying the flooding time with a fixed rest time – Stage EI with 48 h of flooding and 12 h of rest and Stage EII with 36 h of flooding and 12 h of rest; the third stage with effluent recirculation (two tides) – Stage EIII with 6 h of flooding, 6 h of rest and effluent recirculation with 6 h of flooding and 6 h of rest; and the fourth stage EIV with recirculation and oxygenation of the effluent – Stage EIV with 6 hours of flooding, 6 hours of rest and recirculation of the oxygenated effluent in the recirculation reservoir, with another 6 hours of flooding and 6 hours of rest. The results obtained showed satisfactory levels of removal. Emerging contaminants EE2 and TCS achieved maximum removal of 85% and 97% in step EIV. For N-Amon, NT, and PT, the maximum removal also occurred in the EIV step, with values of 89%, 75%, and 78%, respectively. While for carbonaceous organic matter, the maximum removal occurred in step EI for BOD5 (98%) and in step EIII for COD (90%). The reduction of emerging contaminants showed a positive correlation (Pearson) with the removal of N-Amon and NT, indicating that the decrease in EE2 and TCS in the WCTF system may be related to the nitrification process under aerobic conditions. Effluent recirculation and oxygenation were the operational strategies that most influenced the structure and abundance of the microbial community. The presence of potential microorganisms in the process of simultaneous nitrification and denitrification, Dechloromonas, Zoogloea and Acinetobacter, was verified, which may have acted in the removal of carbonaceous and nitrogenous organic matter, as well as in the removal of emerging contaminants EE2 and TCS. Considering the overall performance of the system, it is considered that the EIV stage presented the best performance, the multiple tides and the intensification of nitrification further improve the removal of nitrogenous and phosphorous organic matter and the emerging contaminants EE2 and TCS.